Severe Hypokalemia Probably Associated With Sertraline Use. (February 2014) - Izgi, Cemil; Erdem, Guliz; Mansuroglu, Denyan; Kurtoglu, Nuri; Kara, Mujdat; Gunesdogdu, Fusun
Objective: To report a case of ventricular fibrillation caused by severe hypokalemia probably associated with sertraline use.Case Summary: A 48-year-old male patient experienced ventricular fibrillation and cardiac arrest 2 hours after an uneventful coronary angiography procedure, which revealed normal, unobstructed coronary arteries. Blood chemistry was immediately obtained, revealing a very low potassium (K + ) level of 2.44 mEq/L. Other blood electrolytes, including magnesium, ECG, and corrected QT intervals, were all within normal limits. A thorough search for an etiology of hypokalemia, including adrenal gland causes, herbal product consumption, and toxic exposure, did not reveal any identifiable cause. This led us to consider the only drug he was on—sertraline 50 mg per day—as the possible culprit.Discussion: There has been no clear identification of severe hypokalemia associated with sertraline use in the literature. However, there have been a considerable number of self-reported cases of hypokalemia in patients on sertraline therapy. Scoring according to the Naranjo adverse drug reaction scale revealed a probable relationship between severe hypokalemia and sertraline use in our patient. No clear pathogenic mechanism for the effect of sertraline on serum K equilibrium is known. However, considering the number of self-reported incidences and this case report, the effect of sertraline on serum K levels warrants consideration.Conclusions: This is the first documented case report of severe hypokalemia probably associated with sertraline use.